Determinants of Green Financing Implementation - Suprapto, Galih; Muljaningsih, Sri; Badriah, Nurul (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose : The severity of climate change and environmental degradation continuing to worsen, the implementation of sustainable development principles in a variety of industries, including Islamic banking, is becoming increasingly important. Islamic banks, which have values that support sustainability, have a strategic role to play in supporting green finance, which refers to the financing of projects that have a positive impact on the environment, such as renewable energy and waste management. Green finance is something that Islamic banks have a strategic role to play in supporting sustainable practices. To be more specific, the purpose of this study is to investigate the influence that green policies, green customers, green operations, and green products have on green financing in Islamic financial institutions. There are a number of factors that fall under this category, including banking products that support sustainability, green operational management, the preferences of customers who are becoming increasingly environmentally conscious, and the policies and regulations that are implemented by banks. Design/methodology/approach : The application of quantitative methods is the primary focus of this study, which is primarily concerned with the analysis of the customers of the Bank Jatim Syariah Kediri Branch. A sample size of seventy-five individuals was utilised for the purpose of data collection. This was accomplished through the utilisation of research instruments and primary data that was obtained directly from the source. Among the methods that are associated with data analysis is the technique known as multiple linear regression analysis. Finding : The green products, green operations, and green policies significantly support green financing, whereas, green customers have no significant effect on green financing. Therefore, banks are advised to continue developing green products, optimising green operations through digital technology, strengthening green policies with clear targets, and engaging customers through education and sustainable products. Paper type : Research type